Effectiveness Of Using Hot Jelly Belt in Reducing Pain Disminore in Latest Adolescents at STIKES AS Syifa Kisaran - Ririn Anggriani Sitorus; Selvi Puspan Sari (Institute of Computer Science (IOCS), 2022)
Menstrual pain is a symptomatic phenomenon including abdominal pain, cramps, back pain. Applying a warm compress using the principle of conducting heat through conduction will improve blood circulation and reduce muscle tension in the area of pain. The purpose of this study was to reduce dysmenorrhea pain in late adolescents by using the Hot Jelly Belt. This type of research used a quasi-experimental research design with a pretest posttest control group design. The sampling technique used was purposive sampling with a sample of 60 late adolescents (18-21 years old). Analysis test with wilcoxon signed rank test. Based on the results of the statistical test, the chi square test obtained a significant p-value of 0.018 <α 0.05, which means that there is a difference in dysmenorrhea pain before and after using the hot jelly belt in adolescents. These results prove that the use of hot jelly belts to reduce dysmenorrhea pain in adolescents is proven effective.